2017
DOI: 10.1002/acp.3322
|View full text |Cite
|
Sign up to set email alerts
|

Observers' Language Proficiencies and the Detection of Non‐native Speakers' Deception

Abstract: We examined whether observers' language proficiencies affected their abilities to detect native and non-native speakers' deception. Native and non-native English speakers were videotaped as they either lied or told the truth about having cheated on a test. A total of 284 laypersons-who were either native or non-native English speakers themselves-viewed these videos and indicated whether they believed that the speakers were being truthful or deceptive. Observers were more accurate when judging native speakers t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 43 publications
1
16
1
Order By: Relevance
“…(), Leach et al . (), and Leach and Da Silva () who found more of a truth bias for native speakers than for non‐native speakers. The only, seemingly, contradictory finding comes from Bond and Atoum () who found a truth bias towards non‐natives.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…(), Leach et al . (), and Leach and Da Silva () who found more of a truth bias for native speakers than for non‐native speakers. The only, seemingly, contradictory finding comes from Bond and Atoum () who found a truth bias towards non‐natives.…”
Section: Discussionmentioning
confidence: 95%
“…Speaking in a second language can result in increased communication apprehension, nervousness, anxiety, and cognitive strain (Gregersen, ). The verbal and non‐verbal behaviours associated with these processes are often linked with deception and may be the reason that non‐native speakers are perceived as less credible than native speakers (Castillo, Tyson, & Mallard., ; Da Silva & Leach, ; Elliott & Leach, ; Evans, Pimentel, Pena, & Michael, ; Leach, Snellings, & Gazaille, ; Lev‐Ari & Keysar, ). But how do interviewees, speaking in their non‐native language, perceive their own experience?…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a new phase in the field, researchers have begun to examine the factors unpinning these differences in decision‐making. For example, speakers' accents (Akehurst et al, ), the demands of the deception task (Evans et al, ), and observers' familiarity with non‐native speech (e.g., Evans & Michael, ; Leach, Snellings, & Gazaille, ) have been tested as moderators of proficiency effects. The role of cognitive load has also received significant empirical attention (e.g., Evans et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…These studies have contrasted bilinguals' deception performance in a native versus second language with mixed findings: some observed that deception was more successfully detected in a first than a second language (Akehurst, Arnhold, Figueiredo, Turtle, & Leach, 2018;Leach, Snellings, & Gazaille, 2017), some found the opposite (Evans, Michael, Meissner, & Brandom, 2013), and some found no difference between the two languages (Caldwell- Harris & Ayçiçeği-Dinn, 2009;Cheng & Broadhurst, 2005;Duñabeitia & Costa, 2015;Evans & Michael, 2014). However, language background may influence bilinguals' deception performance across both languages (Elliott & Leach, 2016;Evans, Pimentel, Pena, & Michael, 2017), and yet comparisons between monolingual and bilingual speakers on deception tasks are lacking.…”
mentioning
confidence: 99%